2022
DOI: 10.3390/ijerph191912451
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Does Not Reflect the %VO2max in Recreational Runners during the Marathon

Abstract: Exercise physiologists and coaches prescribe heart rate zones (between 65 and 80% of maximal heart rate, HRmax) during a marathon because it supposedly represents specific metabolic zones and the percentage of O2max below the lactate threshold. The present study tested the hypothesis that the heart rate does not reflect the oxygen uptake of recreational runners during a marathon and that this dissociation would be more pronounced in the lower performers’ group (>4 h). While wearing a portable gas exchange s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
1
0
0
Order By: Relevance
“…Our findings revealed that stride amplitude exhibits the highest entropy during the marathon. The fact that heart rate demonstrates low entropy but a general upward trend during the race indicates that heart rate is not a rapid adjustment variable during the marathon, as previously reported [ 3 , 4 , 33 ]. Importantly, our results demonstrate a strong correlation between the distance at which stride length entropy decreases below 50% of its maximal value (referred to as the entropy maximal reserve, EMR) and marathon performance, as well as the distance at which RPE exceeds a value of 15 (indicating a very difficult race).…”
Section: Discussionsupporting
confidence: 67%
“…Our findings revealed that stride amplitude exhibits the highest entropy during the marathon. The fact that heart rate demonstrates low entropy but a general upward trend during the race indicates that heart rate is not a rapid adjustment variable during the marathon, as previously reported [ 3 , 4 , 33 ]. Importantly, our results demonstrate a strong correlation between the distance at which stride length entropy decreases below 50% of its maximal value (referred to as the entropy maximal reserve, EMR) and marathon performance, as well as the distance at which RPE exceeds a value of 15 (indicating a very difficult race).…”
Section: Discussionsupporting
confidence: 67%